ผลของการใช้ชุดการเรียนรู้ผ่านแท็บเล็ตร่วมกับแนวคิดเกมมิฟิเคชันเพื่อส่งเสริมผลสัมฤทธิ์ทางการเรียนวิชาคณิตศาสตร์ของนักเรียนชั้นประถมศึกษาปีที่ 4 ที่มีความสามารถทางการเรียนแตกต่างกัน - ชาญช่าง จิรชพรรณ (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this study were to (1) make a comparison between the pretests and post-tests of students based on a tablet-based instructional package with gamification concept, and (2) study the relationship between student ability level and instructional procedure with learning achievement. The participants were 60 fourth grade students from Chulalongkorn University Demonstration Elementary School in the second semester of academic year 2017. The findings were found as follows: (1) the post-test of students under the use of “utilization of tablet-based instructional package with gamification concept” was higher than the pretest at a statistical significance level of .05. In contrast, the post-test of students under the use of “utilization of tablet-based instructional package” was not higher than the pretest at a statistical significance level of .05, and (2) the student ability level and instruction procedure did not have any relationship with the learning achievement at a statistical significance level of .05 (F = 0.693, Sig. = 0.504)